Interventionsalltag: Zu den Selbst- und Fremdverständnissen deutscher Intervenierender in Kriegs- und Krisengebieten - Bake, Julika (transcript, 2018)
Are soldiers different? This qualitative-empirical study focuses on the versatile daily lives of those who intervene in war and conflict regions (and questions common assumptions).